PROBABILITAS PULIH PADA BALITA KURUS DAN KURUS SEKALI MENURUT KEPATUHAN MENGIKUTI PEMULIHAN SECARA RAWAT JALAN DI KLINIK GIZI BOGOR - Sri Muljati; Heryudarini Heryudarini; Reviana Reviana; Effendi Rustam (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2007)
THE PROBABILITY OF NUTRITIONAL STATUS IMPROVEMENT AMONG WASTING CHILDREN ACCORDING TO ROUTINE VISITS TO KLINIK GIZI BOGOR.Background: Prevalence of malnutrition on todler in Indonesia still high. It's an indication that nutrition prevention is not yet safisfiying. SKRT 2004 data shows that 9.3% todler in the cities and 11.1% In the village include in category at thin and very thin. Data from departement of health of RI 2005, Prevalence of malnutrition on todler is still on 19.2% and severe malnutrition is 8.8%. Bogor nutritional clinic is already develop severe malnutrition treament by out patient.Aims: To analize data of nutritional clinic visitors on 2001-2005. To now the probability of cured until Z_skore ≥ -2.5 SD dan Z_skore ≥ -2.0 SD, by using weight for height index on thin todlers and very thin todlers after six months of treatment. Methods: 294 todlers are devided in to two categories, which are 192 thin subject (≥-3SD s/d <-2 SD) and 102 very thin (<-3 SD) or thin with clinical indication. Inclution criteria in this anallsis, that the subject doesn't have such as down syndrome, heart disorder, thalasemia, hydrocephalus and microcephalus. Results: The study revealed that father education, mother age, todler age and compliance of treatment were correlated with probability of cured until Z_skore ≥ -2.5 SD dan Z_skore ≥ -2.0 SD, on thin todlers and very thin todlers after six months of treatment.Keywords: severe wasting, under five years, compliance